Comparative study on molecular and higher-order structures of legume seed protein isolates: Lentil, mungbean and yellow pea. (15th June 2023) - Shrestha, Smriti; van 't Hag, Leonie; Haritos, Victoria; Dhital, Sushil
Highlights: Globulin proteins' composition varied among legume seed protein. Lentils and pea globulin comprised of both legumin-like and vicilin-like. Mungbean globulins richer in vicilin-like protein. Globulin protein composition regulate the thermal stability. Protein secondary structure influenced by thermal processing. Abstract: Lentils and mungbean proteins are under-researched compared to pea and soybean. Lentils (green, red and black-lentils), mungbean and yellow pea protein isolates were obtained by alkaline extraction (pH 9)-isoelectric precipitation (pH 4.5) and investigated for molecular and higher-order structures using complementary and novel approaches. These extracted isolates showed comparable protein content but significantly greater nitrogen solubility index (NSI > 85 %) than commercial pea and soy protein isolates (NSI < 60 %). Based on molecular weight estimations from sodium dodecyl sulphate–polyacrylamide gel electrophoresis analysis, the soluble proteins of lentils and yellow pea were identified as legumin-like and vicilin-like, while mungbean was dominated by vicilin-like proteins. The soluble extracts were confirmed to be in native structural condition by size exclusion chromatography and nano-differential scanning calorimetry, unlike commercial extracts. Further differences in secondary structure were evident on circular dichroism spectra of the soluble extracts and deconvolution of the Amide I region (1700–1600 cm −1 ) from Fourier Transform Infrared of the total protein.